(untitled) - Katie Wales (Cambridge, New York, 1990)
The book is a major reference work of the terminology used in stylistics together with its related disciplines of discourse analysis, text linguistics, literary theory and literary criticism. It contains over 600 alphabetically-listed entries drawing widely on areas such as sociolinguistics, semiotics, grammar, communication theory, poetics and traditional rhetoric
Keywords: language and languages - style - handbooks, manuals, etc,style, literary - handbooks, manuals, etc,stylistics